The adaptive capability of the operational team to respond to challenges in the Emergency Centre. A SenseMaker® study in Emergency Centres within Cape Town - Cunningham, Charmaine (Division of Emergency Medicine, 2020)
Background Emergency centres (ECs) serve as a main entry point for patients into hospitals, and patients that present here are undifferentiated with varying levels of acuity. Uncertainty, interruptions, multiple – often conflicting – priorities, and gaps in information flow are inherent to EC work practices, making it a high-risk environment for operational failure. The EC team, the core of which is formed by doctors and nurses, needs the ability to collaboratively and reliably sense and respond to the constant change and flux of information. This depends on the interactions and sense-making of the EC team. Objectives People give meaning to situations through the process of sense-making; they then subjectively construct their reality and share it via plausible stories regarding their situation and environment. The main objective of this study was to explore the collective team-based sense-making of the operational challenges and decisions within the EC. This interprofessionalstudy focused on the dynamics and negotiations within the EC as a complex adaptive system. Methods This exploratory study used narrative-based inquiry with abductive reasoning to meet the objectives. It was divided into two sections. The first was a thick description of the EC context, daily operations and processes. Then, using the SenseMaker® tool, we captured stories about a situation that stood out to participants, and thus mattered to them. Using this novel method, once they told their story, the storytellers self-analysed their stories within a specially designed framework. The results were then explored to find patterns based on the perspectives of sense-making. Results There is no proof of interprofessional sense-making in the EC, and if it occurs it is due to the informal networks between doctors and nurses, and despite formal structure. There is an operational disconnect between doctors, nurses and management, which is caused by information asymmetry, poor feedback loops and disparate communication channels. Because there is no collective sense-making, the EC team is vulnerable to operational failure and crises. Currently, they respond to operational challenges via quick fixes that result in constant firefighting, the impact of which could be seen by the extensive use of war-related metaphors in their stories.